Sacrococcygeal Immature Teratoma in a Twin Pregnancy - Chi-Feng Su; Lap-Hau Cheung; Gin-Den Chen; Yang-Tse Shih; Maw-Sheng Lee (Elsevier, 2005)
Objective: Sacrococcygeal teratoma (SCT) is the most common congenital tumor of the newborn. About 20% of SCTs are malignant. We report the case of a dizygotic twin with a large immature SCT who was successfully delivered by cesarean section at 34 weeks' gestation and who underwent surgical removal of the tumor. Case Report: A 21-year-old, gravida 2, para 0, abortus 1, woman was referred to Chung Shan Medical University (CSMU) Hospital at 33 weeks' gestation because of the diagnosis of a twin pregnancy with SCT in one twin. There were no remarkable findings by ultrasound examination during the second trimester. At 30 weeks of gestation, a sacral mass measuring 8.4 cm in diameter and with multi-cystic and solid components attached to the coccyx was identified sonographically. The patient was referred to CSMU Hospital and underwent planned cesarean section at 34 weeks of gestation. The sick twin was delivered smoothly and underwent surgical resection of the tumor at 1 week of age after magnetic resonance imaging studies. Immature SCT with free surgical margins was confirmed by pathologic examination. The infant did well postoperatively. Conclusion: SCT diagnosed before birth can be managed by planned abdominal delivery and postnatal surgery. Patients with immature teratomas should be followed-up long-term for recurrence and distant metastases.